Factors related to memory absence and delusional memories in patients in intensive care units managed with light sedation. (August 2020) - Noguchi, Ayako; Hosokawa, Koji; Amaya, Fumimasa; Yokota, Isao
Abstract: Objectives: Currently, light sedation is typically given to patients in intensive care units and studies have not extensively examined the factors related to absences or abnormalities of their memories. We, therefore, analysed the factors related to the absence/abnormalities of patients' memories in intensive care units. Research Methodology: A secondary analysis of previously collected survey data examining patients' experiences in an intensive care unit was undertaken (n = 405; women = 38%; median age = 70 years). To observe absent or distorted memories, patients were interviewed after leaving the intensive care unit. We analysed key factors through content analysis of the interviews and field notes. Setting: The intensive care unit of a university hospital. Main outcome measure: Patients' absent or distorted memories after leaving the intensive care unit. Results: Half the patients reported an absence of memories. This was associated with old age and with longer duration of mechanical ventilation. Absent or fragmentary memories were not distressing. Fragmentary and fearful intensive care unit memories were associated with being older. Delusional memories, some of which reflected actual events, were present in 3% of patients. Conclusion: Absence of memories were not distressing, delusional memories occurred less and these memories could comprise of an event in ICU that is difficult for patients to understand.